Dialectal Variations In The Egyptian Edraak Media Video Podcast: A Dialectological Study - Jambak, Mellinda Raswari; Muasssomah; Abdul Basid (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Dialectal variations reflect the richness of culture and the identity of communities, particularly in Arabic, which encompasses a wide range of dialects. This study focuses on the phonological and morphological variations in the Egyptian Amiyah dialect as used in the Edraak Media podcast, specifically the episode "الأمومة وسنينها مع مي إبراهيم" (Motherhood and Its Years with Mai Ibrahim). The aim of this research is to uncover the forms of dialectal variation in a digital context. The study employs a descriptive qualitative method. Primary data include podcast transcripts and audio content, while secondary data are drawn from relevant literature. Data collection is carried out through observation and note-taking, followed by analysis based on the Miles and Huberman model, which involves data reduction, data presentation, and conclusion drawing. The study refers to dialectology theory, which examines linguistic variations based on geographical and social aspects. The findings reveal 24 phonological variations, such as the change of ج to غ and ق to أ, as well as 27 morphological variations, including the use of the prefix ب for progressive actions and ه for the future tense, the use of مش for negation, irregular verb forms, and functional word forms. These variations reflect linguistic simplification for more efficient everyday communication while simultaneously reinforcing local cultural identity. This research contributes to contemporary linguistic studies, particularly in understanding the dynamics of dialects in the digital era. Abstrak  Variasi dialek mencerminkan kekayaan budaya dan identitas masyarakat, khususnya dalam bahasa Arab yang memiliki keragaman dialek yang luas. Penelitian ini berfokus pada variasi fonologi dan morfologi dalam dialek Mesir Amiyah yang digunakan dalam podcast Edraak Media, pada episode "الأمومة وسنينها مع مي ابراهيم". Kajian ini bertujuan mengungkapkan bentuk variasi dialek dalam konteks digital. Penelitian ini menggunakan metode kualitatif deskriptif. Data primer berupa transkripsi dan konten audio podcast, sedangkan data sekunder berasal dari literatur yang relevan. Teknik pengumpulan data dilakukan dengan metode simak dan catat, diikuti analisis berdasarkan model Miles dan Huberman, meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Kajian ini mengacu pada teori dialektologi yang meneliti variasi linguistik berdasarkan aspek geografis dan sosial. Hasil penelitian menunjukkan adanya 24 variasi fonologi, seperti perubahan ج menjadi غ dan ق menjadi أ, serta 27 variasi morfologi, seperti penggunaan prefiks ب untuk tindakan progresif dan ه untuk masa depan, penggunaan مش  untuk negasi, penggunaan bentuk kata kerja yang tidak teratur, dan penggunaan bentuk kata fungsional. Variasi ini mencerminkan penyederhanaan bahasa demi efisiensi komunikasi sehari-hari, sekaligus memperkuat identitas budaya lokal. Penelitian ini berkontribusi pada studi linguistik kontemporer, khususnya dalam memahami dinamika dialek di era digital.